The Effectiveness of Visual Art on the Psychological Response in Stroke Survivors : A Systematic Review - Yoga Ayom Pangestu; Yurike Septianingrum; Imamatul Faizah (Journal Of Nursing Practice, 2023)
Background: Stroke causes disability and has an impact on the psychological needs of patients who are often not met so they are at risk for depression, anxiety, stress, isolation, and other negative impacts. Purpose: This study is a systematic literature review aimed at identifying and discussing the benefits and effectiveness of visual arts interventions on psychological responses in post-stroke patients. Methods: Article searches are performed from Pubmed, ProQuest, Sage, and other search results databases. Results: A total of 8 articles were selected and a discussion was carried out regarding visual art interventions on psychological responses in post-stroke patients. Visual arts therapy (drawing, painting, and digital) has been to be effective for psychological responses in stroke survivors. Conclusion: The benefits and effectiveness of therapy can be felt from 7 to >20 sessions with varying durations for each session. Apart from having a positive impact on psychology, visual arts therapy can also train motor, cognitive, and memory functions in post-stroke patients.